2019
DOI: 10.1542/peds.2019-1286
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated With Safe Infant Sleep Practices

Abstract: OBJECTIVES: To examine prevalence of safe infant sleep practices and variation by sociodemographic, behavioral, and health care characteristics, including provider advice. METHODS: Using 2016 Pregnancy Risk Assessment Monitoring System data from 29 states, we examined maternal report of 4 safe sleep practices indicating how their infant usually slept: (1) back sleep position, (2) separate approved sleep surface, (3) room-sharing without bedsharing, and (4) no soft objects or loose bedding as well as receipt of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 39 publications
2
35
0
2
Order By: Relevance
“…2 A 2017 study in Pediatrics showed that mothers were less likely to place their infant on their belly or side to sleep when they had received advice from a physician consistent with the AAP’s recommendations. 3 In a 2019 study, receiving advice from a physician was associated with a 12%–28% increase in prevalence in safe sleep practices; however, mothers reported that they did not receive consistent advice in aspects of safe sleep beyond “back to sleep.” 4 This finding is consistent with prior literature showing that families often report that they do not receive comprehensive safe sleep advice from their pediatric provider. 5 7 Also, there are demonstrated gaps in pediatrician knowledge about safe sleep practices.…”
Section: Introductionsupporting
confidence: 90%
“…2 A 2017 study in Pediatrics showed that mothers were less likely to place their infant on their belly or side to sleep when they had received advice from a physician consistent with the AAP’s recommendations. 3 In a 2019 study, receiving advice from a physician was associated with a 12%–28% increase in prevalence in safe sleep practices; however, mothers reported that they did not receive consistent advice in aspects of safe sleep beyond “back to sleep.” 4 This finding is consistent with prior literature showing that families often report that they do not receive comprehensive safe sleep advice from their pediatric provider. 5 7 Also, there are demonstrated gaps in pediatrician knowledge about safe sleep practices.…”
Section: Introductionsupporting
confidence: 90%
“…It is possible that the didactic training, the educational brochure, or both produced a rule that established or altered discriminative functions of the stimuli relevant to positioning the infant in the crib. Although the exact source of control for such responding is not clear, these collective outcomes are interesting in that they correspond with caregiver report of being more likely to include soft bedding and an unsafe sleep surface compared to unsafe sleep positioning (Hirai et al, 2019).…”
Section: Discussionmentioning
confidence: 64%
“…Although the exact source of control for such responding is not clear, these collective outcomes are interesting in that they correspond with caregiver report of being more likely to include soft bedding and an unsafe sleep surface compared to unsafe sleep positioning (Hirai et al, 2019). Second, all participants demonstrated perfect responding in the training context following BST, as did all participants from Carrow et al (2020).…”
Section: Percentage Of Correct Responses Per Sessionmentioning
confidence: 62%
See 1 more Smart Citation
“…National surveys including the National Infant Sleep Position Study (National Institute of Child Health and Human Development, 2019) and the Pregnancy Risk Assessment Monitoring System (Shulman, D'Angelo, Harrison, Smith, & Warner, 2018) show that teen mothers are less likely to adhere to recommendations for supine sleeping, bed surfacing (including bed sharing on an adult bed) and other environmental precautions (Bombard et al, 2018;Colson, Geller, Heeren, & Corwin, 2017;Hirai et al, 2019;Phares et al, 2004;Shapiro-Mendoza et al, 2015;Willinger, Ko, Hoffman, Kessler, & Corwin, 2003). Data for US and Arkansas (AR), the site for this study, demonstrate substantial risk.…”
mentioning
confidence: 82%